Bach Music Inc.: Impact of Price Pressure, Capacity Constraints, and a Special Order on Management Decision Making1. (12th December 2017) - Chu, Ling; Libby, Theresa; Mathieu, Robert; Zhang, Ping
Abstract: This case has been developed for an introductory management accounting course at the undergraduate and MBA levels. Although the setting is relatively simple, it illustrates several management accounting issues that are relevant to firms of every size that produce a product or service under competitive pressures and capacity constraints. The case also integrates several topics that are often viewed as abstract by the students. Specifically, it deals with the concepts around cost‐volume profit analysis in a realistic environment, the tension between short‐term and long‐term decisions, discounted cash flow analysis, the impact of managerial incentives and compensation on decision making and the impact of operating leverage on profitability. The case was used successfully several times in an introductory course at the MBA level. Surveys of the students reveal that the case has contributed significantly to their learning and has clarified the concepts introduced in the case.